1993
DOI: 10.1093/jn/123.4.626
|View full text |Cite
|
Sign up to set email alerts
|

Chromium in Human Nutrition: A Review

Abstract: This review summarizes the results of 15 controlled studies supplementing defined Cr(III) compounds to subjects with impaired glucose tolerance. Three of these (3-4 mumol Cr/d for > 2 mo) produced no beneficial effects: serum glucose, insulin and lipid concentrations remained unchanged. The remaining 12 interventions improved the efficiency of insulin or the blood lipid profile of subjects (ranging from malnourished children and healthy middle-aged individuals to insulin-requiring diabetics). In addition, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
342
2
37

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 642 publications
(382 citation statements)
references
References 41 publications
1
342
2
37
Order By: Relevance
“…The hypocholesterolemic effect of supplemental Cr may be related to an augmented insulin action which might have increased lipogenesis and reduced lipolysis, the result being lowered circulatory lipid concentration (Mertz, 1993;Spears, 1999). Interestingly, neither the serum level of glucose nor that of insulin was affected significantly by Cr supplementation in the present study and the average molar ratio between insulin and glucose during the trial period, which was similar across the treatment groups (P .…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…The hypocholesterolemic effect of supplemental Cr may be related to an augmented insulin action which might have increased lipogenesis and reduced lipolysis, the result being lowered circulatory lipid concentration (Mertz, 1993;Spears, 1999). Interestingly, neither the serum level of glucose nor that of insulin was affected significantly by Cr supplementation in the present study and the average molar ratio between insulin and glucose during the trial period, which was similar across the treatment groups (P .…”
Section: Discussionmentioning
confidence: 43%
“…Nevertheless, when subjected to the intravenous glucose loading during the IVGTT, the Cr supplemented goats exhibited improvement in glucose utilisation which is consistent with an enhancement in insulin action. As occurs in human subjects (Mertz, 1993) these subtle changes in insulin action might have influenced lipid metabolism to elicit a hypocholesterolemic effect. Increment in serum insulin level due to Cr supplementation in goats has been reported earlier .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While no strain differences were apparent for measures of glucose response at T1, it was found that glucose had a greater CR and shorter t 1 2 in NZ cows at T2. This indicates greater insulin responsiveness in the NZ cows compared to NA cows in mid-lactation, as insulin resistance is associated with slower CR, longer t 1 2 and a greater AUC for glucose at similar insulin concentrations (Mertz, 1993). Greater insulin responsiveness in the NZ cows in mid-lactation is consistent with the accumulation of more body reserves from midlactation to the end of lactation (Patton et al, 2008).…”
Section: Discussionmentioning
confidence: 61%
“…Chrom trójwartościowy zachowuje prawidłowy metabolizm glukozy poprzez jego udział w czynniku tolerancji glukozy (Glucose Tolerance Factor -GTF). Wykazano, że GTF zawiera aktywną formę trójwartościowego chromu (68). Grela i wsp.…”
unclassified